PEMODELAN TUMPAHAN MINYAK DI TELUK LALONG KABUPATEN BANGGAI - Sabhan, Sabhan; Mudin, Yutdam; Babanggai, Marianus (Natural Science: Journal of Science and Technology, 2014)
Oil distribution  cause environmental problems that disrupt marine ecosystems and reduce the aesthetic value of coastal waters in Gulf  Lalong Banggai. The aims of this study to build a 2D hydrodynamics model to see the patterns  of water mass movement and models of oil spill distribution base on the hydrodynamic models in Gulf of Lalong Banggai Regency (0°57'17,3 "latitude and 122 ° 47'52 " E) with a potential spill, location, volume, and duration of discharge of oil spills. Based on the results of models oil spill distribution in Gulf Lalong Banggai such us waters prone to oil spills.